A qualitative pilot study exploring the acceptability of a peer provider delivered substance use brief intervention from the perspective of youth in Kenya - Florence Jaguga; Matthew C. Aalsma; Leslie A. Enane; Matthew Turissini; Edith Kamaru Kwobah; Edith Apondi; Julius Barasa; Gilliane Kosgei; Yvonne Olando; Mary A. Ott (Substance Abuse Treatment, Prevention, and Policy)
Abstract Background Substance use disorders are prevalent among youth in sub-Saharan Africa (SSA), yet treatment resources are scarce. Peer provider delivered brief interventions (BIs) represent an affordable and potentially scalable strategy for addressing youth substance use disorders. The goal of this study is to assess the acceptability of a peer provider delivered substance use BI from the perspective of youth in Kenya. Methods We conducted qualitative semi-structured interviews with youth participants (n = 25) to explore acceptability of a substance use BI. Youth were participants in a two-arm mixed-methods pilot randomized controlled trial (RCT) investigating the feasibility of a peer provider delivered single-session substance use BI for youth aged 15–24 years with moderate-risk substance use. The semi-structured interviews were conducted three months after the BI was delivered and were guided by the Theoretical Framework of Acceptability (TFA). Qualitative data were analyzed through thematic analysis. Results We interviewed 25 of 38 participants in the BI arm, 18 males and 7 females; 15 were ages 18–24 years, and 10 ages 15–17 years. Affective attitude: Most youth reported that they enjoyed the session content and enjoyed interacting with the peer provider. Burden: Most youth felt that it was easy to understand the session and participate in it. Perceived effectiveness: Most of the youth perceived the intervention to be effective in helping them reduce substance use and improve their well-being. Ethicality: All youth perceived that the counselling session fit in with their goals and values. Intervention coherence: Most youth understood the overall goal of the intervention. They reported that the goal of the intervention was to help youth stop substance use, and to bring about behavior change. Opportunity costs: Some youth reported that they had to forgo other activities to attend the session, such as work, school, sports, gaming, visiting family, or house chores. Self-efficacy: Most youth felt confident about being able to cut down or stop using substances following the intervention. Conclusion and recommendations Our findings indicate that the peer provider delivered single-session substance use BI was acceptable to youth. The youth recommended that follow-up sessions be provided to ensure sustained behavior change. This study supports the utility of the TFA in exploring acceptability of a substance use intervention from the perspective of young people. Trial registration NCT05545904 Registration date 16/09/2022 Registry ClinicalTrials.gov https//clinicaltrials.gov/study/NCT05545904.